Dural sinus collapsibility, idiopathic intracranial hypertension, and the pathogenesis of chronic migraine - De Simone, Roberto; Ranieri, Angelo; Sansone, Mattia; Marano, Enrico; Russo, Cinzia Valeria; Saccà, Francesco; Bonavita, Vincenzo (Neurological sciences, 2019)
Available evidences suggest that a number of known assumption on idiopathic intracranial hypertension (IIH) with or without papilledema might be discussed. These include (1) the primary pathogenetic role of an excessive dural sinus collapsibility in IIH, allowing a new relatively stable intracranial fluids pressure balance at higher values; (2) the non-mandatory role of papilledema for a definite diagnosis; (3) the possibly much higher prevalence of IIH without papilledema than currently considered; (4) the crucial role of the cerebral compliance exhaustion that precede the raise in intracranial pressure and that may already be pathologic in cases showing a moderately elevated opening pressure; (5) the role as “intracranial pressure sensor” played by the trigeminovascular innervation of dural sinuses and cortical bridge veins, which could represent a major source of CGRP and may explain the high comorbidity and the emerging causative link between IIHWOP and chronic migraine (CM). Accordingly, the control of intracranial pressure is to be considered a promising new therapeutic target in CM.